The First Healed Bite Mark and Embedded Tooth in the Snout of a Middle Permian Gorgonopsian (Synapsida: Therapsida) - Benoit, Julien; Browning, Claire; Norton, Luke A. (Frontiers in Ecology and Evolution, 2021)
Despite their significance for paleobiological interpretations, bite marks have been rarely reported in non-mammalian therapsids. Here we describe, for the first time, the occurrence of a tooth embedded in the snout of a gorgonopsian. The tooth is surrounded by a bony callus, which demonstrates that the animal was still alive after the attack and healed. The identity of the attacker is unknown. Two hypotheses are discussed to account for this healed bite: failed predation (most likely by a biarmosuchian, therocephalian, or another gorgonopsian) and intraspecific social biting. Though predation cannot be ruled out, it has been hypothesized that gorgonopsians used their saber-like teeth for social signaling, which suggests that social biting may be the most likely scenario. The practice of social biting has long been hypothesized in non-mammalian therapsids, but this is the first fossilized evidence of the behavior to be described.